Without Bounds: A Scientific Canvas of Nonlinearity and Complex Dynamics - Rubio, Ramon G.; Ryazantsev, Yuri S.; Starov, Victor M.; Huang, Guo-Xiang.; Chetverikov, Alexander P.; Arena, Paolo; Nepomnyashchy, Alex A.; Ferrus, Alberto; Morozov, Eugene G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Bringing together over fifty contributions on all aspects of nonlinear and complex dynamics, this impressive topical collection is both a scientific and personal tribute, on the occasion of his 70th birthday, by many outstanding colleagues in the broad fields of research pursued by Prof. Manuel G Velarde. The topics selected reflect the research areas covered by the famous Instituto Pluridisciplinar at the Universidad Complutense of Madrid, which he co-founded over two decades ago, and include: fluid physics and related nonlinear phenomena at interfaces and in other geometries, wetting and spreading dynamics, geophysical and astrophysical flows, and novel aspects of electronic transport in anharmonic lattices, as well as topics in neurodynamics and robotics.
Preface -- Section 1: Flows, Instabilities and Convective Patterns -- Section 2: Interfacial Phenomena, Wetting and Spreading Problems -- Section 3: Waves and Solitons, and Other Collective Excitations -- Section 4: Complex Dynamics and Stochastic Dynamics -- Section 5: Bio- and Neuro-physical Problems -- Section 6: Geophysical Flows and Other Geo-problems.
Keywords: Physics; Engineering; Hydraulic engineering; Physics; Nonlinear Dynamics; Complexity; Classical Continuum Physics; Soft and Granular Matter, Complex Fluids and Microfluidics; Engineering Fluid Dynamics